Three nights with the princess - Krahn, Betina M. (Zebra historical romance., 2018)
Fiercely independent, and wholly devoted to her subjects, Crown Princess Thera of Mercia must marry before she can become Queen. But the beauty<U+2019>s reluctance to choose a husband has plunged her into peril far from home<U+2014>and into the arms of a handsome rescuer. Powerful, hot-blooded mercenary Saxxe Rouen has better things to do than fight a crowd of drunken brutes. After all, there is little profit in saving a demoiselle in distress<U+2014>or is there? His valor should be repaid, if not in silver, then in another kind of reward: Lovely, fiery Thera will spend one night in his bed. Once safe, Thera didn<U+2019>t expect to face yet another danger<U+2014>her attraction to the beguilingly charming warrior. But as a battle of wits ensues, one night may lead to three. And a proud princess may discover the pleasure of surrendering her heart<U+2014>while Saxxe may find the kingdom, and the love, he was truly meant to win . . .